Reinventing American Protestantism : Christianity in the new millennium - Miller, Donald E. (Donald Earl), 1946- (University of California Press, 1997)
Explores the trend in the last thirty years towards new paradigm churches, sometimes called megachurches or postdenominational churches, which are reinventing Christianity by redefining the institutional forms and reconnecting people to the message of first-century Christianity using the media of twentieth century America.